Changing Professional Behaviors in the Digital World Using the Medical Education e-Professionalism (MEeP) Framework—A Mixed Methods Multicentre Study - Guraya, Shaista Salman; Yusoff, Muhamad Saiful Bahri; Rashid-Doubell, Fiza; Harkin, Denis W.; Al-Amad, Suhail H.; Fredericks, Salim; Halabi, Mouhammad Omar O.; Abdullah, Natasya; Moussa, Hatem; Mallah, Saad Imad Yousef; Sefen, Jessica Atef Nassef; AlKoheji, Heba Khalid A. Rahman Mohamed Ishaq; et al. (Frontiers in Medicine, 2022)
Background: There is increasing evidence on the exponential use of technology-based social media in medical field that has led to a proliferation of unprofessional behaviors in digital realm. Educating, training, and changing the behaviors of healthcare professionals are essential elements to restrain the rising unprofessional incidents. Therefore, this research was designed to determine the impact of an interventional workshop on the medical and dental students in improving their professional behaviors in the digital world using the newly developed medical Education e-Professionalism (MEeP) framework. Methods We adopted the Theory of Planned Behavior (TPB) as a benchmark reference which explores constructs intertwined with the mission-based MEeP framework; values (whistleblowing-raising concerns), behaviors (being responsible in the digital world) and identity (reflective practice in the digital world). A multicentre 3-phased mixed-method study was conducted using a pre-workshop survey, an online interventional workshop, and a post-workshop survey. SPSS and NVivo were the tools used for the data analysis. Results A total of 130 students registered for workshop out of which 120 completed the pre-workshop survey, 62 joined the workshop and 59 completed the workshop and post-workshop survey. From the whistleblowing – raising concern perspective, we found that attitudes and perceived behavioral control had a significant relationship. While for responsible in digital world category, attitude and perceived behavioral control had a significant bearing on the intentions. Third, for reflective practice, attitude and subjective norms significantly enhanced the intention of participants. A multi layered thematic analysis yielded four overarching themes of attitudes, subjective norms, perceived behavioral control and intentions. Most students showed positive attitudes of being reflective, self-directed, and humane. Students realized the subjective norms had made them conscientious, self-aware and conformative. While perceived behavioural control manifested as identity and Intentions were heavily reliant on self-actualization. Conclusion Our mixed method study found that the interventional workshop using MEeP framework significantly improved attitudes, subjective norms, perceived behavioral control, and intentions. This study provides valuable evidence of MEeP framework evaluation using the theoretical underpinning of TPB by reporting positive changes in professional values, behaviors, and identities of undergraduate medical and dental students.